Recombinant thrombomodulin protects against LPS‐induced acute respiratory distress syndrome via preservation of pulmonary endothelial glycocalyx. (14th July 2020) - Suzuki, Kodai; Okada, Hideshi; Takemura, Genzou; Takada, Chihiro; Tomita, Hiroyuki; Yano, Hirohisa; Muraki, Isamu; Zaikokuji, Ryogen; Kuroda, Ayumi; Fukuda, Hirotsugu; Nishio, Ayane; Takashima, Shigeo; et al.
Abstract : Background and Purpose: Disruption of the endothelial glycocalyx is causally related to microvascular endothelial dysfunction, a characteristic of sepsis‐induced acute respiratory distress syndrome (ARDS). Recombinant human thrombomodulin (rhTM) attenuates vascular endothelial injuries, but the underlying mechanism remains elusive. Here, we investigated the structural basis and molecular mechanisms of rhTM effects on vascular endothelial injury in a model of sepsis. Experimental Approach: LPS (20 mg·kg −1 ) was intraperitoneally injected into 10‐week‐old male C57BL6 mice, and saline or rhTM was intraperitoneally injected 3 and 24 h after LPS injection. Using serum and/or lung tissue, histological, ultrastructural, and microarray analyses were performed. Key Results: Survival rate of rhTM‐treated mice was significantly higher than that of control mice 48 h after LPS injection. Serum concentrations of IL‐6 and high‐mobility group box 1 were lower in the rhTM‐treated group than in the control. Injury to the endothelial glycocalyx in pulmonary capillaries was attenuated by rhTM treatment. Gene set enrichment analysis revealed up‐regulation of gene sets corresponding to cell proliferation/differentiation and anti‐inflammation, such as the TGF‐β pathway, and negative regulation of IL‐6, upon rhTM treatment. Gene expression of heparan sulfate 6‐ O ‐sulfotransferase 1 and endothelial cell‐specific molecule 1 (components of the endothelial glycocalyx) was significantly preserved by rhTM treatment, and their protein expression levels were maintained in endothelial cells. Conclusion and Implications: Our findings show that rhTM treatment affected inflammation, cell proliferation/differentiation, and glycocalyx synthesis in serum and lung tissue, subsequently attenuating ARDS caused by endothelial injury. Abstract :